Elide me bare: Null arguments in American Sign Language - Koulidobrova, Elena (Natural language and linguistic theory, 2017)
In this paper, I argue that the traditional analysis of null arguments—subjects and objects—in American Sign Language needs to be re-evaluated. It is typically assumed that in the absence of agreement, the null argument is either a topic-bound variable or a silent pronoun (pro). I introduce novel data that pose a problem for both of these views. As the null argument is subjected to a variety of diagnostics, I demonstrate that it is best analyzed as a case of ellipsis of a non-branching argument of the verb—a bare NP.